Perencanaan dan Pengelolaan Pesantren Darul Abror Melalui Pengembangan Kurikulum PAI - Ramami, Dwi Saprida; Suparta, Suparta; Rifa'i, Andi Arif (PASCASARJANA IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2019)
This study reports on the planning and management of Islamic Boarding School Daarul Abror in developing curriculum of Islamic Education Subject. This study attempts to address the following question; (1) How is the administration management at Islamic Boarding School DaarulAbror? (2) How are the development and implementation Islamic Education Subject at Islamic Boarding School DaarulAbror? It is conducted at Islamic Boarding School Daarul Abror Bangka, Bangka Belitung Islands Province. The data for the study are obtained through two instruments; The interview and observation.The interview is conducted to obtain the clarification and expanation from the boarding school. The observation is done during the interaction in the teaching learning process to observe the activities done in the school. The subject of this study is the vice-head master of the school who has been a teacher as well as curriculum developer in the Islamic Boarding School. The finding reveal that, (1) the administration management at Islamic Boarding School Daarul Abror is conducted based on the educational institutions of the Ministri of Religious Affair and the Ministri of Education and Culture Republic Indonesia. (2) the development of and the implementation of Islamic Education subjetcs is by applying education in a classroom as well as out of classroom refering to the achievement life skill and the Islamic character building in dayly life. Based on the finding it is recommended that the stakeholders of the Islamic Boarding School should keep managing their institution to develope and applying nowdays educational system.